Irx3/5 Null Deletion in Mice Blocks Cochlea-Saccule Segregation and Disrupts the Auditory Tonotopic Map - Fritzsch, Bernd; Weng, Xin; Yamoah, Ebenezer N; Qin, Tianli; Hui, Chi-Chung; Lebrón-Mora, Laura; Pavlinkova, Gabriela; Sham, Mai Har (The Journal of comparative neurology, 2024)
A gene cadre orchestrates the normal development of sensory and non-sensory cells in the inner ear, segregating the cochlea with a distinct tonotopic sound frequency map, similar brain projection, and five vestibular end-organs. However, the role of genes driving the ear development is largely unknown. Here, we show double deletion of the Iroquois homeobox 3 and 5 transcription factors (Irx3/5 DKO) leads to the fusion of the saccule and the cochlear base. The overlying otoconia and tectorial membranes are absent in the Irx3/5 DKO inner ear, and the primary auditory neurons project fibers to both the saccule and cochlear hair cells. The central neuronal projections from the cochlear apex-base contour are not fully segregated into a dorsal and ventral innervation in the Irx3/5 DKO cochlear nucleus, obliterating the characteristic tonotopic auditory map. Additionally, Irx3/5 deletion reveals a pronounced cochlear-apex-vestibular "vestibular-cochlear" nerve (VCN) bilateral connection that is less noticeable in wild-type control mice. Moreover, the incomplete segregation of apex and base projections that expands fibers to connect with vestibular nuclei. The results suggest the mammalian cochlear apex is a derived lagena reminiscent of sarcopterygians. Thus, Irx3 and 5 are potential evolutionary branch-point genes necessary for balance-sound segregation, which fused into a saccule-cochlea organization.
Keywords: brainstem; Mice, Knockout; Cochlea; tectorial membrane; development; sluchová dráha; cochlea; myši knockoutované; sakulus a utrikulus; Animals; Transcription Factors; transkripční faktory; zvířata; kochlea; Auditory Pathways; myši; Saccule and Utricle; Homeodomain Proteins; Mice; homeodoménové proteiny